Oxidative stress and the presence of bacteria increase gene expression of the antimicrobial peptide aclasin, a fungal CSαβ defensin in Aspergillus clavatus - Gabriela Contreras; Nessa Wang; Holger Schäfer; Michael Wink (PeerJ, 2019)
Background Antimicrobial peptides (AMPs) represent a broad class of naturally occurring antimicrobial compounds. Plants, invertebrates and fungi produce various AMPs as, for example, defensins. Most of these defensins are characterised by the presence of a cysteine-stabilised α-helical and β-sheet (CSαβ) motif. The changes in gene expression of a fungal CSαβ defensin by stress conditions were investigated in Aspergillus clavatus. A. clavatus produces the CSαβ defensin Aclasin, which is encoded by the aclasin gene. Methods Aclasin expression was evaluated in submerged mycelium cultures under heat shock, osmotic stress, oxidative stress and the presence of bacteria by quantitative real-time PCR. Results Aclasin expression increased two fold under oxidative stress conditions and in the presence of viable and heat-killed Bacillus megaterium. Under heat shock and osmotic stress, aclasin expression decreased. Discussion The results suggest that oxidative stress and the presence of bacteria might regulate fungal defensin expression. Moreover, fungi might recognise microorganisms as plants and animals do.